Assessing the Effectiveness of Mobile Banking Services Offered by Co-operatives in Nepal - Bidari, Dinesh; Upadhyaya, Shankar Prasad; Sigdel, Niranjan; Sapkota, Ram Babu; Dahal, Keshav Prasad (International Research Journal of MMC, 2023)
Mobile banking plays a vital role in daily transactions and overall performance of any financial institutions. The objective of this study is to assess the utilization and effectiveness of mobile banking services provided by financial cooperative. Descriptive research design was applied by adopting a survey method to collect data. Out of 11 financial cooperatives providing mobile banking, two co-operatives Hatemalo and Upayogi Sahasrabdi Saccos were selected under a random sampling method. Out of 1371 members using mobile banking, 310 were selected for the study as respondents through a purposive sampling method. Questionnaire has been administered with five points Likert scale ranging from strongly disagree (1) to strongly agree (5). The results show that utilization of mobile service was less than average and effectiveness of mobile banking was moderately high (4). Satisfaction level between genders was the same (4) but older age group and low education level had lower satisfaction level. It is concluded that cooperatives should organize broad member education and mobile banking training campaign to increase mobile banking service utilization. It is also suggested to the curriculum development of Nepal to introduce mobile banking subjects at secondary school levels.